Analisis Kondisi Sosial Ekonomi Petani Hutan Kemasyarakatan Alam Lestari Resort Jangkok KPH Rinjani Barat: Analysis of the Socio-Economic Conditions of Farmers in the Alam Lestari Community Forest at Jangkok Resort, Rinjani Barat Forest Management Unit - Harun, Anandita Cika Maharani; Markum, Markum; Ningsih, Rima Vera (HUTAN TROPIKA, 2024)
This study aims to analyze the socioeconomic conditions of farmers in the Alam Lestari Community Forest (HKm), Jangkok Resort, West Rinjani Forest Management Unit (KPH). The approach used is qualitative descriptive, with purposive sampling to select 71 respondents from two Forest Farmer Groups (KTH). The analyzed variables include farmers' social characteristics, livelihood diversity, income, and poverty levels. Data were collected through observation, interviews, and questionnaires, and analyzed using descriptive methods. The results show that most farmers have a low education level, their primary occupation is farming, and they cultivate less than 0.5 hectares of land. The main income sources are non-timber forest products (NTFPs) such as durian, coffee, and cocoa. Poverty level analysis based on World Bank standards indicates that most farmers live above the poverty line and are considered prosperous. Socially, farmers' participation in HKm management is relatively high, especially in physical activities such as communal work. However, access to cooperative institutions remains low due to a lack of trust. This study concludes that HKm management contributes to improving farmers' economic conditions, although challenges related to land access and institutional participation need to be addressed for program sustainability.